LITERASI DIGITAL DAN MANAJEMEN MEDIA SOSIAL UNTUK HUMAS SEKOLAH BERBASIS AGAMA DI KOTA SURAKARTA - N. Rahmanto, Andre; Anshori, Mahfud; Priliantini, Anjang; Faridl Widhagdha, Miftah; Tri Hendriyani, Christina; Nailul Amal, Nora (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
The development of digital technology and social media has increased public vulnerability to hoaxes, fake news, and hate speech. The ministry of Communication and Informatics noted that there are 800 thousand hoax content per year, with the majority spread through social media in the form of provocation and hate speech related to SARA. Research shows that low digital literacy, especially in educational institutions, has an impact on this group being vulnerable to provocation and missinformation. To overcome this problem, education and assistance are needed, especially in digital literacy and social media management in educational institutions. For this reason, this community service program aims to equip public relations of religious-based educational institutions, namely Muhammadiyah on Surakarta City with these skills. The target ist o reduce the spread of hoaxes and teach these skills to colleagues and students. This community service activity uses the socialization method and focus group discussion (FGD) involving 27 public relations practitioners from school representative under the Muhammadiyah foundation in Surakarta city. The indicator of the success of this activity is the increase in participants’ understanding of digital literacy and social media management as evidenced by the pre test and post test provided. The result of this community service activity is an increase in the post test score from 38.89 to 90.74. This shows an increase in the understanding of Muhammadiyah school public relations in Surakarta city in managing the school’s official social media. — Perkembangan teknologi digital dan media sosial telah meningkatkan kerentanan publik terhadap hoaks, berita palsu, dan ujaran kebencian. Kementerian Komunikasi dan Informatika mencatat terdapat 800 ribu konten hoaks per tahun dengan mayoritas tersebar melalui media sosial dalam bentuk provokasi dan hate speech terkait SARA. Penelitian menunjukkan bahwa rendahnya literasi digital, terutama di lembaga pendidikan, memberikan dampak pada kelompok ini rentah terhadap provokasi dan misinformasi. Untuk mengatasi masalah ini, diperlukan edukasi dan pendampingan khususnya dalam literasi digital dan manajemen media sosial di lembaga pendidikan. Untuk itu, program pengabdian kepada masyarakat ini bertujuan untuk membekali humas lembaga pendidikan berbasis keagamaan, yakni Muhammadiyah di Kota Surakarta dengan keterampilan tersebut. Targetnya adalah mengurangi penyebaran hoaks dan mengajarkan keterampilan ini kepada kolega serta siswa. Kegiatan pengabdian kepada masyarakat ini menggunakan metode sosialisasi dan diskusi kelompok terarah atau focus group discussion (FGD) yang melibatkan 27 orang praktisi humas dari perwakilan sekolah di bawah yayasan Muhammadiyah di Kota Surakarta. Indikator keberhasilan dari kegiatan ini adalah bertambahnya pemahaman peserta terkait literasi digital dan manajemen media sosial yang dibuktikan dengan pre test dan post test yang disediakan. Hasil dari kegiatan pengabdian kepada masyarakat ini adalah peningkatan skor post test dari 38,89 menjadi 90,74. Hal ini menunjukkan adanya peningkatan pemahaman humas sekolah Muhammadiyah di Kota Surakarta dalam mengelola media sosial resmi sekolah.